Computational model for evaluating the state of geomechanical systems during computing experiments - Fomychov, V.; Pochepov, V.; Fomychova, L.; Lapko, V. (Розробка родовищ, 2017)
Purpose. To create a model allowing integration of the diverse features identified for the rock massif behavior by differentiation of various theories and real phenomena into a single information-analytical flow.
Findings. Sample tables were obtained containing the acceptable values of weight characteristics for the various simulated elements in the generalized computational domain. A recursive algorithm for the analysis of the studied objects description’ efficiency in the solution of geomechanics problems by grid numerical methods was formulated and implemented as a computational module. The authors created a system for the assessment of the results obtained via computational experiment at the time of full-scale investigation, which provides a comprehensive analysis of changes in the rock massif state during the operation of the selected support system. The conditions of combining the design characteristics of the simulated support elements functioning in a single load-carrying system under dynamic redistribution of forces were obtained.
Originality. The resulting generalized model of mine working and elements affecting its condition allows to determine most accurately the nature of changes in the stress-strain state of geotechnological system regardless of the originally a priori specified limitations. Цель. Создать модель, позволяющую интегрировать все многообразие выявленных особенностей поведения горного массива путем дифференциации различных теорий и реальных явлений в единый информационно-аналитический поток.
Результаты. Получены типовые таблицы, содержащие допустимые величины весовых характеристик для различных моделируемых элементов в обобщенной расчетной области. Сформулирован и реализован в виде расчетного модуля рекурсивный алгоритм анализа эффективности описания исследуемых объектов при решении задач геомеханики сеточными численными методами. Создана система оценки получаемых результатов вычислительного эксперимента при проведении натурных исследований обеспечивающая комплексный анализ изменения состояния породного массива в ходе эксплуатации выбранной системы крепления. Получены условия совмещения расчетных характеристик моделируемых элементов крепи функционирующих в единой грузонесущей системе при динамическом перераспределении усилий.
Научная новизна. Полученная обобщенная модель горной выработки и элементов, влияющих на ее состояние, предельно точно позволяет определять картину изменения напряженно-деформированного состояния геотехнологической системы независимо от первоначально априори заданных ограничений. Мета. Створити модель, що дозволяє інтегрувати все різноманіття виявлених особливостей поведінки гірського масиву шляхом диференціації різних теорій і реальних явищ у єдиний інформаційно-аналітичний потік.
Результати. Отримано типові таблиці, що містять припустимі величини вагових характеристик для різних елементів, які моделюються в узагальненій розрахунковій області. Сформульовано й реалізовано у вигляді розрахункового модуля рекурсивний алгоритм аналізу ефективності опису досліджуваних об’єктів при рішенні завдань геомеханіки сітковими чисельними методами. Створено систему оцінки одержуваних результатів обчислювального експерименту при проведенні натурних досліджень, яка забезпечує комплексний аналіз зміни стану породного масиву в ході експлуатації обраної системи кріплення. Отримано умови сполучення розрахункових характеристик елементів кріплення, які моделюються й функціонують у єдиній вантажонесучій системі при динамічному перерозподілі зусиль.
Наукова новизна. Одержана узагальнена модель гірничої виробки й елементів, що впливають на її стан, гранично точно дозволяє визначати картину зміни напружено-деформованого стану геотехнологічної системи незалежно від початкових апріорі заданих обмежень.